Cross-cultural measurement invariance of the multidimensional competitive orientation inventory: Non-clinical samples in South Korea and Hungary - Taeyoon Aum; Márta Fülöp; Seoyoung Kim; Jeongeun Diana Lee; Dong-gwi Lee (PLoS ONE, 2025)
The Multidimensional Competitive Orientation Inventory (MCOI) aims to assess competitive orientations including self-developmental, hypercompetitive, avoidant, and indifferent attitudes. The present study tested its cross-cultural applicability and examined cross-national differences between South Korea ( n = 350) and Hungary ( n = 343), taking cultural traits into account. Using a revised 10-item version (two low-loading items removed), multi-group CFA with WLSMV supported configural and scalar invariance across countries. Factor variances were invariant, whereas factor covariances were not, indicating that inter-factor correlations differed across countries despite a shared structure. For criterion validity analyses, we conducted cross-group comparisons only for measures that demonstrated invariance; noninvariant measures were interpreted within each country. Overall, the results suggest that the MCOI can be used cross-culturally with appropriate scale adjustment. However, competitive orientations may manifest differently across individualistic and collectivistic cultures in both the motivations for and consequences of competition, underscoring the need for further research. Implications for the practical use of the MCOI and directions for future research are discussed.